THE EFFECT OF ONLINE LEARNING METHODS VIA ZOOM MEETING ON CRITICAL THINKING ABILITY OF NURSING STUDENTS - Widiyono .; Atik Aryani; Fajar Alam Putra (Jurnal Keperawatan Malang, 2022)
Background : Critical thinking is an essential component of nursing by using its knowledge thoroughly in order to provide effective care. In achieving the goal of critical thinking skills in students, an educational process is needed. However, during the COVID-19 pandemic, almost every university in Indonesia conducts a distance learning system or online via Zoom Meeting. Distance learning is used as the implementation of social distancing. Objective: This study was conducted to determine the effect of using the Zoom Meeting application on the critical thinking skills of nursing students in medical surgical nursing courses during the COVID-19 pandemic. Methods: This study used the Quasy experimental pre-post design method. The intervention provided was learning via Zoom Meeting for 1 semester in the medical surgical nursing course. The number of samples is 32 students. Data collection techniques were carried out by measuring critical thinking skills through Google Forms and Whatsapps to Nursing students. Results: This study shows that critical thinking skills in students' critical research respondents increased based on the results of the Paired t-Test, which obtained a statistically significant value (p> 0.05). Conclusion: the advantages of using Zoom Meetings are considered practical and efficient for students, because communication between students and lecturers is easier than communicating in writing or via chat. Keywords: Learning Method, Online, Zoom Meeting, Nursing, Critical Thinking.